Health promotion and prevention of bowel disorders through toilet designs: A myth or reality? - Sudip Bhattacharya; Vijay Kumar Chattu; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2019)
Now, lifestyle diseases are quite common globally. The risk factors of lifestyle diseases such as sedentary habits, lack of physical exercise, and lack of fiber result in the development of noncommunicable diseases. However, when the point of discussion slightly shifted toward toilet habits, it is always seems to be a secret affair. In fact, the discussion of defecation-related matter openly is considered a taboo. This is not uncommon even in medical fraternity. In fact, during the early 1980s, some researches on the association between the diarrhea prevalence, open-air defecation, and latrine use rate were documented. However, nobody acknowledges it socially desirable, now, to discuss defecation-related issues. The public health experts completely ignored the discussion of ill-effects of the use of pedestal latrine on human health. It is evident from scientific studies over a period, that many of the abdominal disorders of the human due change in his toilet habits from a squatting-to-sitting posture using a pedestal latrine. That disease correlation was ignored at that time. The increase in disease burden is due to nonmaintaining the ergonomic design during the construction of this kind of toilets. Squatting posture for the defecation is the most appropriate way, as in this case, abdominal muscles work actively and complete evacuation takes place. To conclude, the time has come to reacquaint people with their natural habits and put this unfortunate experiment to an end.